19F CEST imaging probes for metal ion detection. Issue 30 (25th July 2017) - Peng, Qiaoli; Yuan, Yaping; Zhang, Huaibin; Bo, Shaowei; Li, Yu; Chen, Shizhen; Yang, Zhigang; Zhou, Xin; Jiang, Zhong-Xing
Abstract : An easily available fluorinated chelator was developed as a highly sensitive 19 F iCEST MRI probe for selectively detecting metal ions. Abstract : For detecting metal ions with 19 F chemical exchange saturation transfer magnetic resonance imaging ( 19 F CEST MRI), a class of novel fluorinated chelators with diverse fluorine contents and chelation properties were conveniently synthesized on gram scales. Among them, a DTPA-derived chelator with high sensitivity and selectivity was identified as a novel 19 F CEST imaging probe for simultaneously detecting multiple metal ions.